Solar Simulator for Photovoltaic Devices Based on the Electrodeless Sulfur Lamp - Frolova, T. I.; Frolov, A. (My University, 2018)
At the present time, there has been an active growth in the use of solar energy, which is the most affordable renewable energy source for us. In this regard, there is a need for testing of photovoltaic cells and solar panels used to collect solar energy. In laboratory conditions, when testing photovoltaic panels, it is necessary to use solar simulators, which have very close parameters to solar radiation. The most important components of solar imitators are artificial light sources. Within this work, the reference spectral distribution of sunlight in the visible optical range at the level of AM 1.5G was shown, as defined in ASTM Gl73-03. The goal of this work is to determine the output characteristics (spectral match and spatial non-uniformity of irradiance) of the solar simulator based on ASTM E927-10 standard in the interval of 400 nm - 700 nm. As a light source of the solar simulator, a powerful electrodeless sulfur lamp with microwave excitation is used which has a continuous quasi-solar spectrum of optical radiation with a maximum at 510 nm and is very close to the solar spectrum in the visible range.
Keywords: solar simulator; photovoltaic device; sunlight; electrodeless sulfur lamp; wavelength